IMPLEMENTASI STRATEGI PEMASARAN DENGAN MENGGUNAKAN BLUE OCEAN STRATEGY PADA PERUSAHAAN SOSIS - Agustriyana , Darwis (Majalah Bisnis & IPTEK, 2016)
The purpose of this study was to examine, analyze and propose changes that can be done to address the problems raised in the formulation of the problem through the analysis of marketing strategies using the Blue Ocean Strategy. The method used is descriptive method. The results showed that the decline in product sales is due to several factors. These factors are in terms of the product itself, in terms of packaging, the destination cities in terms of product marketing as well as promotional and advertising products. Problems sales decline may be addressed by the Blue Ocean Strategy. The proposed factors described in the Strategy Canvas namely variety of nutrients and vitamins, originality, taste, and their slogan ’HEALTHY IS CHEAP’ as a result of their product differentiation in the form of vegetable sausage. Keywords: marketing strategy; blue ocean strategy; strategy canvas.